Counteracting selection for antibiotic-resistant bacteria. Issue 1 (2nd January 2016) - Yosef, Ido; Manor, Miriam; Qimron, Udi
ABSTRACT: The occurrence of antibiotic-resistant bacterial pathogens is on the rise because antibiotics exert selection pressure that kills only the antibiotic-sensitive pathogens. Sanitation and cleansing of hospital surfaces and the skin of medical personnel do not counteract this selective pressure, but rather indiscriminately reduce total pathogens on treated surfaces. Here, we discuss two recently introduced genetic strategies, based on temperate bacteriophages as DNA-delivery vehicles, that aim to sensitize bacteria to antibiotics and selectively kill the antibiotic-resistant ones. Outlooks for rendering one such approach more efficient and applicable are proposed. We believe that using an end product designed according to the provided principles on hospital surfaces and in hand-sanitizers will facilitate substitution of antibiotic-resistant pathogens with sensitive ones.